2012
DOI: 10.1063/1.3697832
|View full text |Cite
|
Sign up to set email alerts
|

Electron temperature in electrically isolated Si double quantum dots

Abstract: Charge-based quantum computation can be attained through reliable control of single electrons in lead-less quantum systems. Single-charge transitions in electrically-isolated double quantum dots (DQD) realised in phosphorus-doped silicon can be detected via capacitively coupled single-electron tunnelling devices. By means of time-resolved measurements of the detector's conductance, we investigate the dots' occupancy statistics in temperature. We observe a significant reduction of the effective electron tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…We now turn to the filter performance measured by the device electron temperature T e with a GaAs quantum dot thermometer, [32][33][34][35][36][37][38][39][40] comparing T e with and without filters. For all measurements below, the sample wires are connected to the room temperature measurement setup through $1.5 m long thermo-coax cables, 41 which are very effective attenuators above a few GHz, see green curve in Fig.…”
mentioning
confidence: 99%
“…We now turn to the filter performance measured by the device electron temperature T e with a GaAs quantum dot thermometer, [32][33][34][35][36][37][38][39][40] comparing T e with and without filters. For all measurements below, the sample wires are connected to the room temperature measurement setup through $1.5 m long thermo-coax cables, 41 which are very effective attenuators above a few GHz, see green curve in Fig.…”
mentioning
confidence: 99%
“…Remote detection has, therefore, made it unnecessary to have an electrical current flow and has led to the realization of systems in which only one lead or none is used [12,[15][16][17][18][19][20][21]. While the absence of 2DEG reservoirs can be beneficial to both suppress thermal fluctuations induced by electrical noise [22,23] and conveniently scale up these systems, hysteretic behaviour is observed that may complicate the tuning of charge states [24,25]. Such hysteresis can, however, be exploited for the implementation of single-electron memory devices [26,27].…”
mentioning
confidence: 99%
“…Typically, non-invasive and sensitive charge readout is achieved by means of on-chip electrometers 1,2 . The scope of applicability of these sensing techniques is quite broad, ranging from charge noise characterization [3][4][5] to cryogenic thermometry [6][7][8] , as well as Maxwell's demon implementations 9,10 and quantum metrology [11][12][13] . Arguably, one of the research fields that has more largely benefitted from advancements in charge sensing is solid-state quantum information processing [14][15][16][17][18] .…”
mentioning
confidence: 99%